Performance Evaluation of Drip Irrigation System in Grapes Field in Tamil Nadu, India - A. Valliammai; M. Nagarajan; E. Sujitha (Research Advances in Environment, Geography and Earth Science Vol. 3, 2024)
Field evaluation of the drip irrigation unit is important. It is important to establish whether the desired emitter discharge uniformity specifications are being met and to decide whether the system can be operated efficiently. A commercial drip irrigation system was evaluated at a farmer’s field under grapes to study the various parameters, viz., emission uniformity, emitter flow variations and statistical uniformity during the year 2019. The soil characteristics of the experiment field at different profile depths were analyzed and sandy loam soil is available at 0 to 15 cm depth and sandy clay loam is available from 15 cm to 60 cm depths, Irrigation was given daily based on potential evaporation. The soil moisture status during the crop growth period at various depths under the emitter was studied. The soil moisture in the field was maintained in a range of 21 to 23% under drip irrigation in the 60 cm depth irrespective of the duration. During the rainy season when no irrigation was given, the soil moisture fluctuated depending upon the intensity of rainfall. The system performance was good as indicated by the high uniformity coefficient (93%) which indicates that the field was irrigated in a highly uniform manner. In contrast to the rainy period, there is an increase in the soil moisture content with respect to depth. This increase is also identical as reflected by the gradient of the soil moisture profile. The yield was estimated as 27500 kg/ha and water use efficiency was found to be 566 kg.ha/cm. The study revealed that the superiority of drip irrigated soil regime and moisture content in the soil at 60 cm depth was more or less maintained constantly during the irrigation period.